Anna Mirga Kruszelnicka, Jekatyerina Dunajeva (eds.): Re-Thinking Roma Resistance throughout History: Recounting Stories of Strength and Bravery: Budapest: European Roma Institute for Arts and Culture (ERIAC) 2020, 252 s.,ISBN: 978-3-9822573-0-3 - Stachová, Monika (Romano džaniben, 2022)
RECENZE